Pengembangan Media Audio Visual Bahasa Indonesia Berbasis Hots Materi Hidup Bersih dan Sehat (Penelitian Design And Development di Kelas II SD Negeri Kedokan) - Salma Namiroh (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is motivated by the lack of procurement of variety of learning media integrated with technology in thematic learning of clean and healthy living materials, especially in Indonesian language learning. This makes students find it difficult to receive learning materials. In addition, the demands of 21st century education also require integrating learning with technology and developing high-level thinking skills or HOTS. Based on this, the researcher intends to develop indonesian audio visual media based on HOTS clean and healthy living materials for students of grade II of Kedokan State Elementary School. This research uses design and development methods with addie model. Based on the results of validation provided, the research products that have been developed by researchers fall into the category of